Sovereign exposures of European banks: It is not all doom - Martien Lamers; Thomas Present; Rudi Vander Vennet (Journal of Risk and Financial Management, 2022)
We investigate whether sovereign bond holdings of European banks are determined by a risk-return trade-off. Using data between 2011 and 2018 for 75 European banks, we confirm that banks exhibited risk-taking behavior during the sovereign debt crisis, e.g., due to moral suasion. In the period 2015-2018, however, banks' investments in sovereign bonds are characterized by sound risk-return considerations, suggesting a lessening of the doom loop. This result is mainly driven by banks in the core European countries, as banks in the GIPS countries do not exhibit such behavior, nor do they avoid riskier bonds following the sovereign debt crisis.
Keywords: G11; G18; G21; G28; 330; sovereign exposures; risk-return trade-off; bank-sovereign nexus; doom loop; Sharpe ratio